A novel polysulfone–polyvinylpyrrolidone membrane with superior proton-to-vanadium ion selectivity for vanadium redox flow batteries. Issue 4 (17th December 2015) - Wu, Chunxiao; Lu, Shanfu; Wang, Haining; Xu, Xin; Peng, Sikan; Tan, Qinglong; Xiang, Yan
Abstract : Outstanding performance in VRFBs: a novel polysulfone–polyvinylpyrrolidone membrane with high ion selectivity, superior stability and low cost is constructed for VRFBs. The VRFB with the PSF–PVP–50 membrane exhibits impressive CE (98%), EE (89%), and excellent stability during the 2000 h continuous charge–discharge cycling test. Abstract : A novel kind of effective vanadium ion-suppressed polysulfone–polyvinylpyrrolidone (PSF–PVP) membrane with high ion selectivity, superior stability and low cost is designed and constructed for vanadium redox flow batteries (VRFBs). The VRFB with the PSF–PVP–50 membrane exhibits impressive coulombic efficiency (98%) as well as energy efficiency (89%), and outstanding stability during the 2000 h continuous charge–discharge cycling test.